#TITLE_ALTERNATIVE# - MUHAMMAD MUJIB (NIM 12206068); Pembimbing: Dr. Ir. Taufan Marhaendrajana, ECEP
Single Stage Test compressive test is a tool for studying the strength properties of reservoir rock, reservoir rock is modeled into the laboratory conditions. Results of measurement on the surface conditions in general have different results with the actual conditions at the reservoir conditions, therefore, the working principle of the tool is considered the principal stress acting on the reservoir rock and reservoir modeling the detailed conditions such as high temperature conditions, the pore pressure and the effects of the presence of fluid in the reservoir rock. Such a laboratory model will give you a level of influence of stress, both the maximum stress or minimum stress acting on the reservoir rock and the influence of temperature and presence of fluid to the reservoir rock strength properties. SST in design by considering the existing reservoir conditions in Indonesia, generally described by a large axial takanan (overbourden pressure) reaches a maximum radial pressure of 4000 psia and that can act as confining pressure (pore pressure) reaches a maximum of 1500 psia and temperatures reach 400 oF. This paper will explain in detail about the design tools report the results of SST and compression testing using a synthetic core of this tool.